Unraveling the Effect of Singlet Oxygen on Metal-O2 Batteries: Strategies Toward Deactivation - Ruiz de Larramendi, Idoia; Ortiz-Vitoriano, Nagore (Frontiers in Chemistry, 2020)
Aprotic metal-O2 batteries have attracted the interest of the research community due to their high theoretical energy density that target them as potential energy storage systems for automotive applications. At present, these devices show several practical problems, which hinder the attainment of the high theoretical energy densities. Among the main limitations, we can highlight the irreversible parasitic reactions that lead to premature death of the battery. The degradation processes, mainly related to the electrolyte, lead to the formation of secondary products that accumulate throughout the cycling in the air electrode. This accumulation of predominantly insulating products results in the blocking of active sites, promoting less efficiency in system performance. Recently, it has been discovered that the superoxide intermediate radical anion is involved in the generation of the reactive oxygen singlet species (1O2) in metal-O2 batteries. The presence of singlet oxygen is intimately linked to electrolyte degradation processes and carbon-electrode corrosion reactions. This review analyzes the nature of singlet oxygen, while clarifying its toxic role in metal-O2 batteries. In addition, the main mechanisms of deactivation of singlet oxygen are presented, with the aim of inspiring the research community in the development of new molecules that will be capable of mitigating the harmful effects related to this highly reactive species.